NIRS calibration database on fresh cassava puree to predict cooking time - Tran, Thierry; Davrieux, Fabrice; Belalcazar Martinez, John Eiver (2023)
This database contains 542 NIR spectra of cassava puree acquired in CIAT (Colombia), by using FOSS DS2500 NIR spectrometer. Cassava harvested at CIAT (Colombia) from various fields and years: 2022: 1 field "progeny" in January and February 2022. 2 harvests (trials) Field 202108CQQU2_ciat (M RTB): 22-02 and 22-05 on 12 Jan. and 8 Feb. 2022, repectively (10 and 11 MAP) This database contains also laboratory data measured on the same cassava roots samples: water absorption at 20 minutes of cooking (WA20) and water absorption at 30 minutes of cooking (WA30) the Dry matter values (DM) correspond to predicted values using a specific claibration developped by CIAT. Spectra included in this database have been acquired using: BELALCAZAR, J., TRAN, T., MEGHAR, K., & DAVRIEUX, F. (2021). NIRS Measurement on Fresh Ground Cassava. High-Throughput Phenotyping Protocols (HTPP), WP3. Cali, Colombia: RTBfoods Laboratory Standard Operating Procedure, 9 p. (2022-10-18)